Broadly Neutralizing Antibody VRC01 Prevents HIV-1 Transmission from Plasmacytoid Dendritic Cells to CD4 T Lymphocytes - Su, Bin (American Society for Microbiology, 2014)
Plasmacytoid dendritic cells (pDC) poorly replicate human immunodeficiency virus type 1 (HIV-1) but efficiently transfer HIV-1 to adjacent CD4 T lymphocytes. We found that coculture with T lymphocytes downregulates SAMHD1 expression, enhances HIV-1 replication, and increases pDC maturation and alpha interferon (IFN-α) secretion. HIV-1 transfer to T lymphocytes is inhibited by broadly neutralizing antibody VRC01 with efficiency similar to that of cell-free infection of T lymphocytes. Interestingly, prevention of HIV-1 transmission by VRC01 retains IFN-α secretion. These results emphasize the multiple functions of VRC01 in protection against HIV-1 acquisition.